Concentration of Fluoride Ion in Surface Soils in Vallioor Union of Tirunelveli District, Tamil Nadu, India - Santhi, D.; Umayoru Bhagan, V.; Lekshmana Sarma, R. (Asian Journal of Chemistry, 2010)
The excessive intake of fluoride ion in drinking water beyond the prescribed limits leads to dental and skeletal fluorosis. Similarly the surface soils and rocks containing fluoride in many parts of the world lead to health problems even to cattle and human beings by means of plants and crops. Physico-chemical properties viz., pH, electrical conductivity, fluoride content of surface soils in fluorotic as well as control areas were analysed by comparative study in the southern parts of Vallioor Union of Tirunelveli district, Tamil Nadu. More than 50% of the people are affected by fluoride in drinking water and surface soils. This study unfolds the fact that the presence of fluoride in surface soils is highly sporadic in the areas under study and the fluorotic concentration varies from 2.88 ppm to 9.82 ppm.